EVALUATION OF THE EFFECT OF THE NUMBER OF HAMMERS, CLEARANCE, SIEVE OPENING AND THEIR INTERACTIONS ON SOME PERFORMANCE INDICATORS OF THE CORN HAMMER MILL - Ali khairullah Dhahir ‎; Assad yousif khudher ‎ (University of Thi-Qar Journal of agricultural research, 2025)
Due to the difficulty of standardizing hammer mill machine settings due to the many design factors affecting their performance and the varying operating conditions, a factorial experiment was conducted using three factors: number of hammers (8 and 10), clearance (2.5 mm, 5 mm, and 7.5 mm), and screen opening (2.5 mm, 4 mm, and 8 mm). The aim was to evaluate the impact of the main factors and their interactions on some machine performance indicators (productivity, specific energy consumption rate, and the average geometric diameter of processed yellow maize grains), determine the percentage of importance of the factors, and determine the best combination of machine numbers before starting milling. The results showed that the number of hammers and clearance, along with their interaction with the sieve opening, had a slight effect on productivity, specific energy consumption, and geometric mean diameter compared to the sieve opening effect. The sieve opening effect was 100%, compared to 7% and 4% for clearance and number of hammers, respectively. A combination of 2.5 mm sieve opening with any of the two factors can be used for fine grinding, and 8 mm sieve opening with any of the two factors can be used for coarse grinding within the experimental limits